PLURALISTIC AND MULTICULTURAL EDUCATION IN THE INDONESIAN SCHOOLS - Paul Suparno (Sanata Dharma University Yogyakarta, 2017)
Indonesia consists of many islands, cultures, ethnicities, and religions. This country will be strong if its people would like to live and work together peacefully. It can be done if they accept their differences and want to work together as one nation. The spirit should be taught since the elementary schools until universities. Thus, the curriculum, teachers, and teacher training institutes should be pluralistic and multicultural. Indonesian schools should provide and improve the pluralistic and multicultural spirit and environment, because there are still many obstacles in these matters.DOI: https://doi.org/10.24071/ijiet.2017.010102